Seismic velocity and anisotropy tomography of southern Sumatra - Liu, Yongsheng (2022)
In this study new isotropic P- and S-wave velocity models as well as the P-wave azimuthally anisotropic model of the crust and uppermost mantle beneath southern Sumatra are derived from regional earthquake data by using the eikonal equation-based seismic tomography method. All the tomographic results reveal a clear high-velocity (high-V) belt in the uppermost mantle that represents the subducting Indo-Australian slab. In the mantle wedge, relatively low velocity (low-V) anomalies are clearly imaged, which may be related to the ascending fluids and partial melts caused by slab dehydration. The P-wave azimuthally anisotropic model shows complex patterns in the upper crust, which may be due to the effects of the maximum horizontal compressive stress and/or geological structure. Trench-normal fast velocity directions (FVDs) prevail in the lower crust, which may be associated with the plastic flow induced by the oblique plate convergence. Predominant trench-parallel FVDs in the fore-arc and volcanic-arc mantle wedge and trench-normal FVDs in the back-arc mantle wedge are observable, which are possibly related to 2-D slab-driven corner flow and/or 3-D complex mantle flow. The subducting slab generally displays trench-parallel FVDs, suggesting that the slab may keep the original fossil anisotropy.